Marine microalgae Schizochytrium demonstrates strong production of essential fatty acids in various cultivation conditions, advancing dietary self-sufficiency - Literáková, Petra; Zavřel, Tomáš; Búzová, Diana; Kaštánek, Petr; Červený, Jan (Frontiers in Nutrition, 2024)
Introduction Polyunsaturated fatty acids (PUFAs) are essential nutrients that humans obtain from their diet, primarily through fish oil consumption. However, fish oil production is no longer sustainable. An alternative approach is to produce PUFAs through marine microalgae. Despite the potential of algae strains to accumulate high concentrations of PUFAs, including essential fatty acids (EFAs), many aspects of PUFA production by microalgae remain unexplored and their current production outputs are frequently suboptimal. Methods In this study, we optimized biomass and selected ω-3 PUFAs production in two strains of algae, Schizochytrium marinum AN-4 and Schizochytrium limacinum CO3H. We examined a broad range of cultivation conditions, including pH, temperature, stirring intensity, nutrient concentrations, and their combinations. Results We found that both strains grew well at low pH levels (4.5), which could reduce bacterial contamination and facilitate the use of industrial waste products as substrate supplements. Intensive stirring was necessary for rapid biomass accumulation but caused cell disruption during lipid accumulation. Docosahexaenoic acid (DHA) yield was independent of cultivation temperature within a range of 28–34°C. We also achieved high cell densities (up to 9 g/L) and stable DHA production (average around 0.1 g/L/d) under diverse conditions and nutrient concentrations, with minimal nutrients required for stable production including standard sea salt, glucose or glycerol, and yeast extract. Discussion Our findings demonstrate the potential of Schizochytrium strains to boost industrial-scale PUFA production and make it more economically viable. Additionally, these results may pave the way for smaller-scale production of essential fatty acids in a domestic setting. The development of a new minimal culturing medium with reduced ionic strength and antibacterial pH could further enhance the feasibility of this approach.